Defective cancellous bone structure and abnormal response to PTH in cortical bone of mice lacking Cx43 cytoplasmic C-terminus domain - Pacheco-Costa, Rafael (Bone, 2015)
Connexin43 (Cx43) forms gap junction channels and hemichannels that allow the communication among osteocytes, osteoblasts, and osteoclasts. Cx43 carboxy-terminal (CT) domain regulates channel opening and intracellular signaling by acting as a scaffold for structural and signaling proteins. To determine the role of Cx43 CT domain in bone, mice in which one allele of full length Cx43 was replaced by a mutant lacking the CT domain (Cx43(ΔCT/fl)) were studied. Cx43(ΔCT/fl) mice exhibit lower cancellous bone volume but higher cortical thickness than Cx43(fl/fl) controls, indicating that the CT domain is involved in normal cancellous bone gain but opposes cortical bone acquisition. Further, Cx43(ΔCT) is able to exert the functions of full length osteocytic Cx43 on cortical bone geometry and mechanical properties, demonstrating that domains other than the CT are responsible for Cx43 function in cortical bone. In addition, parathyroid hormone (PTH) failed to increase endocortical bone formation or energy to failure, a mechanical property that indicates resistance to fracture, in cortical bone in Cx43(ΔCT) mice with or without osteocytic full length Cx43. On the other hand, bone mass and bone formation markers were increased by the hormone in all mouse models, regardless of whether full length or Cx43(ΔCT) were or not expressed. We conclude that Cx43 CT domain is involved in proper bone acquisition; and that Cx43 expression in osteocytes is dispensable for some but not all PTH anabolic actions.